Including biogeochemical factors and a temporal component in benthic habitat maps: Influences on infaunal diversity in a temperate embayment - Radke, L.; Huang, Z.; Przeslawski, R.; Webster, I.; McArthur, M.; Anderson, T.; Siwabessy, Justy; Brooke, B. (CSIRO Publishing, 2011)
Mapping of benthic habitats seldom considers biogeochemical variables or changes across time. We aimed to: (i) develop winter and summer benthic habitat maps for a sandy embayment; and (ii) compare the effectiveness of various maps for differentiating infauna. Patch types (internally homogeneous areas of seafloor) were constructed using combinations of abiotic parameters and are presented in sediment-based, biogeochemistry-based and combined sedimentbiogeochemistry-based habitat maps. August and February surveys were undertaken in Jervis Bay, NSW, Australia, to collect samples for physical (% mud, sorting, % carbonate), biogeochemical (chlorophyll a, sulfur, sediment metabolism, bioavailable elements) and infaunal analyses. Boosted decision tree and cokriging models generated spatially continuous data layers. Habitat maps were made from classified layers using geographic information system (GIS) overlays and were interpreted from a biophysical-process perspective. Biogeochemistry and % mud varied spatially and temporally, even in visually homogeneous sediments. Species turnover across patch types was important for diversity; the utility of habitat maps for differentiating biological communities varied across months. Diversity patterns were broadly related to reactive carbon and redox, which varied temporally. Inclusion of biogeochemical factors and time in habitat maps provides a better framework for differentiating species and interpreting biodiversity patterns than once-off studies based solely on sedimentology or video-analysis. © 2011 CSIRO.